The Relationship Between Anxiety Levels and the Occurrence of Hyperemesis Gravidarum - Monica Marcelina Kindangen; Nila Widya Keswara (Lembaga Pengembangan Kinerja Dosen, 2025)
Hyperemesis gravidarum is a condition of severe nausea and vomiting during pregnancy that can cause serious physical and psychological effects on pregnant women. In addition to biological and hormonal factors, psychological aspects such as anxiety are thought to play an important role in the occurrence of hyperemesis gravidarum. This study aims to analyze the relationship between the level of anxiety in pregnant women and the occurrence of hyperemesis gravidarum. The study uses a quantitative approach with an analytical observational design through a cross-sectional method. The study sample consisted of 30 pregnant women in their first trimester who were selected using purposive sampling. Anxiety levels were measured using a standardized anxiety questionnaire and categorized as moderate and severe anxiety, while the incidence of hyperemesis gravidarum was determined based on complaints of excessive nausea and vomiting and clinical data. Data analysis was performed univariately and bivariately using the Goodman–Kruskal tau test with a significance level of 0.05. The results showed that most respondents experienced moderate to severe anxiety, and some respondents experienced hyperemesis gravidarum. Bivariate analysis showed a significant and very strong relationship between anxiety levels and the incidence of hyperemesis gravidarum. These findings indicate that the higher the anxiety level of pregnant women, the greater the likelihood of hyperemesis gravidarum. The conclusion of this study confirms that anxiety is an important psychological factor associated with the occurrence of hyperemesis gravidarum. Therefore, the integration of anxiety screening and management into antenatal care is essential as part of a comprehensive, mother-centered approach to pregnancy care